MENGEMBANGKAN KERJASAMA (SOFT SKILL) MELALUI PENERAPAN METODA COOPERATIF LEARNING DAN EXPERIENTIAL LEARNING DALAM MATA KULIAH PSIKOLOGI KEWIRAUSAHAAN - lala septiyani sembiring (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
This research aimed to examine the effect of the value of student co-operation in enterpreneur courses through the implementation of co-operative learning and experiential teaching method. Research was conducted on 57 psychology students who take enterpreneur courses treated in method cooperative teaching and experiential learning. Data collected through the scale were analyzed using the t test to see differences in the ability of co-operation between the students before teaching method experiential learning and cooperative learning with teaching method after doing experiential learning and cooperative learning. T test results prove that there are significant differences between the data pre and post data. This study means that there is a significant difference in the value of co-operation caused by the treatment by student cooperative learning and experiential learning method.